Physical fitness of primary school children in the reflection of different levels of gross motor coordination - Ingrid Ružbarská (Palacký University Olomouc, 2016)
Background: Lower level of motor competences may result in unsuccessful engaging of children in physical activities as early as pre-school age and also prepubescent ages. This may subsequently lead to a spiral of forming negative attitudes towards an active lifestyle and may be accompanied by a negative trend in weight status and physical fitness outcomes. Objective: The aim of the study was to identify and analyze differences in physical fitness and somatic parameters of primary school-aged children according to level of their gross motor coordination. Methods:  A sample of 436 children aged 7 to 10 years, of which were 222 girls and 214 boys, performed physical fitness tests - Eurofit test battery. The level of motor coordination was assessed using the test battery Körperkoordination-Test-für-Kinder (KTK). The anthropometric data (body mass, body height, sum of five skinfolds) were measured. The one-way ANOVA was used to assess differences in physical fitness test items and anthropometry parameters between children with normal motor quotient (MQ ≥ 86) and decreased levels of gross motor coordination (MQ ≤ 85). Results: Research findings indicate a strongly negative trend in physical development of children with motor deficits (MQ ≤ 85). The results of ANOVA revealed significantly less favourable level of most of the assessed physical fitness parameters in children with decreased level of motor coordination. Conclusions: The findings suggest that physical fitness outcomes of primary school-aged children are associated with a lower level of motor coordination. Motor coordination probably plays an important role in preventing, or moderating the so-called negative trajectory leading to childhood overweight or obesity.